Extracellular Vesicles Induce an Aggressive Phenotype in Luminal Breast Cancer Cells Via PKM2 Phosphorylation - Kang, Seo Young; Lee, Eun Ji; Byun, Jung Woo; Han, Dohyun; Choi, Yoori; Hwang, Do Won; Lee, Dong Soo (Frontiers in Oncology, 2021)
Background: Aerobic glycolysis is a hallmark of glucose metabolism in cancer. Previous studies have suggested that cancer cell–derived extracellular vesicles (EVs) can modulate glucose metabolism in adjacent cells and promote disease progression. We hypothesized that EVs originating from cancer cells can modulate glucose metabolism in recipient cancer cells toinduce cell proliferation and an aggressive cancer phenotype. Methods: Two breast cancer cell lines with different levels of glycolytic activity, MDA-MB-231 cells of the claudin-low subtype and MCF7 cells of the luminal type, were selected and cocultured as the originating and recipient cells, respectively, using an indirect coculture system, such as a Transwell system or a microfluidic system. The [18F]fluorodeoxyglucose (FDG) uptake by the recipient MCF7 cells was assessed before and after coculture with MDA-MB-231 cells. Proteomic and transcriptomic analyses were performed to investigate the changes in gene expression patterns in the recipient MCF7 cells and MDA-MB-231 cell-derived EVs. Results: FDG uptake by the recipient MCF7 cells significantly increased after coculture with MDA-MB-231 cells. In addition, phosphorylation of PKM2 at tyrosine-105 and serine-37, which is necessary for tumorigenesis and aerobic glycolysis, was highly activated in cocultured MCF7 cells. Proteomic profiling revealed the proliferation and dedifferentiation of MCF7 cells following coculture with MDA-MB-231 cells. Transcriptomic analysis demonstrated an increase in glycolysis in cocultured MCF7 cells, and the component analysis of glycolysis-related genes revealed that the second most abundant component after the cytoplasm was extracellular exosomes. In addition, proteomic analysis of EVs showed that the key proteins capable of phosphorylating PKM2 were present as cargo inside MDA-MB-231 cell-derived EVs. Conclusions: The phenomena observed in this study suggest that cancer cells can induce a phenotype transition of other subtypes to an aggressive phenotype to consequently activate glucose metabolism via EVs. Therefore, this study could serve as a cornerstone for further research on interactions between cancer cells.